Defragment Structure Think Student in Finish Problem Math on Error Read and Understand reviewed from Newman's theory - Heri Sopian Hadi (Jurnal Scientia, 2023)
The structure of thinking is an internal representation of students' mental activity that describes the flow of solving mathematical problems. The structure of thinking is one of the factors that influence students' math problem solving errors. Therefore, mistakes made by students in solving math problems require the right solution, one of which is defragmentation. The purpose of this study was to defragment the thinking structure of junior high school students towards reading errors based on Newman's theory in solving math problems. The approach used in this research is qualitative with descriptive research type. Subject selection was carried out by purposive sampling technique with criteria, namely students who had reading errors and understanding errors. The research data consisted of answers, recordings of semi-structured interview results and students' think aloud results. The analysis techniques are reducing data, presenting data, and drawing conclusions. The results of the research show that defragmentation can help students to rearrange their thinking structures. This is evidenced by the complete structure of students' thinking from the stages of interpreting/understanding, applying, analyzing, and evaluating.